2022
DOI: 10.1136/ard-2022-222451
|View full text |Cite
|
Sign up to set email alerts
|

Distinct immune-effector and metabolic profile of CD8+T cells in patients with autoimmune polyarthritis induced by therapy with immune checkpoint inhibitors

Abstract: ObjectivesRheumatic immune-related adverse events (irAE) such as (poly)arthritis in patients undergoing immune checkpoint inhibitor (ICI) treatment pose a major clinical challenge. ICI therapy improves CD8+ T cell (CD8) function, but CD8 contributes to chronic inflammation in autoimmune arthritis (AA). Thus, we investigated whether immune functional and metabolic changes in CD8 explain the development of musculoskeletal irAE in ICI-treated patients.MethodsPeripheral CD8 obtained from ICI-treated patients with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…ICI affect T cell immune function. T cells infiltrate the organ and cause an immune activation response ( 5 , 6 ), which destroys pancreatic beta cells and leads to absolute insulin deficiency, namely type 1 diabetes. Type 1 diabetes can be divided into delayed type 1 diabetes, acute type 1 diabetes, or fulminant type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…ICI affect T cell immune function. T cells infiltrate the organ and cause an immune activation response ( 5 , 6 ), which destroys pancreatic beta cells and leads to absolute insulin deficiency, namely type 1 diabetes. Type 1 diabetes can be divided into delayed type 1 diabetes, acute type 1 diabetes, or fulminant type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Arthritis in course of ICIs is mostly polyarticular and seronegative in 80% of the cases, thus hardly distinguishable from seronegative RA (34). Pathogenetically, ICIs can induce Th17 cell activation and proliferation, changes in CD8 immune-effectors profile, and impaired regulatory T cell survival (35,36). A specific role of the IL-17 axis also in seronegative RA, if any, remains to be investigated.…”
Section: Immunopathogenesismentioning
confidence: 99%
“…A recent molecular study demonstrated that CD8 + T cells from ICI-treated patients who developed arthritis had distinct effector functions and metabolic profiles from those from ICI-treated patients who remained arthritis-free and that TNF-α inhibitors or Janus kinase (JAK) inhibitors were unable to adequately correct such dysfunction in vitro [ 98 ]. This suggests that bDMARDs and JAK inhibitors may effectively reduce symptoms but may not fundamentally restore T cell function, although because of the risk of malignancy [ 99 ], JAK inhibitors are normally avoided in ICI-induced arthritis.…”
Section: Rheumatic Iraesmentioning
confidence: 99%